Speech enhancement through information gap filling technique - Serrano-Bersosa, Joselito Francisco; Guamán-Luna, Martha Magdalena (EPISTEME KOINONIA, 2022)
This study investigates English language use with classroom students after applying the Information Gap Filling Technique (IGT) at the Paiguara public school in San Juan-Gualaceo, Ecuador. A sample of 22 students (12 boys and 10 girls) from the third level of BGU was selected. The research was conducted in two phases. The quantitative part used a pre- and post-test of oral interaction and in the qualitative part, a questionnaire with open-ended questions. The findings of the study showed that students increased their use of English in the classroom as a result of the application of IGT in the variables of comprehension, grammar, vocabulary, fluency and pronunciation with values of (0.37, 0.50, 0.27, 0.05, 0.32) respectively. Consequently, the Information Gap-filling technique has proved to be effective in promoting the use of English language in classrooms as a means of communication.